2021
DOI: 10.1097/md.0000000000028141
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing identified a novel CACNA1A I1379F variant in a familial hemiplegic migraine type 1 pedigree

Abstract: Rationale: Familial hemiplegic migraine (FHM) is a rare, autosomal dominant migraine with aura. CACNA1A encodes the α1A subunit of P/Q-type voltage-gated calcium channels, and its mutations have been associated with a wide spectrum of episodic and chronic neurological disorders, including FHM type 1 (FHM1). Patient concerns: A Chinese girl and some of her relatives who presented with hemiplegia with or without migraine were found to carry a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Recent guidelines for HM suggest oral flunarizine at 10 mg/day but this recommendation was largely based on studies in adults with no focus on CACNA1A-caused HM ( 5 , 6 ). Instead, previous CACNA1A-related cases showing the efficacy of flunarizine were both at the daily dose of 5 mg, involving one FHM1 family and noteworthily, a woman suffering from episodic ataxia and HM ( 9 , 10 ). A study summarizing 11 years' experience in treating childhood migraine found flunarizine effective in HM at an initial dose of 5 mg daily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent guidelines for HM suggest oral flunarizine at 10 mg/day but this recommendation was largely based on studies in adults with no focus on CACNA1A-caused HM ( 5 , 6 ). Instead, previous CACNA1A-related cases showing the efficacy of flunarizine were both at the daily dose of 5 mg, involving one FHM1 family and noteworthily, a woman suffering from episodic ataxia and HM ( 9 , 10 ). A study summarizing 11 years' experience in treating childhood migraine found flunarizine effective in HM at an initial dose of 5 mg daily.…”
Section: Discussionmentioning
confidence: 99%
“…EA2 and HM can coexist within the same family ( 7 , 8 ) and even in the same patient ( 9 ). The similarity of symptoms and signs makes the diagnosis of these disorders difficult, highlighting that genetic testing is necessary ( 4 , 10 ). Brain MRI of EA2 patients typically reveals cerebellar atrophy or no notable findings, with cerebral white matter appearing to be rarely affected ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation